Cytopathological tests for early detection of oral carcinogenesis. Issue 1 (January 2020) - Salgueiro, Arthur P.; Martelli, Francine T.; D'Ávila, Stéphanie R.; Milnikel, Tainara R.; Koehler-Santos, Patricia; Maraschin, Bruna J.; da Silva, Viviane P.; Rados, Pantelis V.; Visioli, Fernanda
Abstract : The carcinogenesis in the oral cavity occurs as a multistep process and is often preceded by potentially malignant lesions. The main risk factors for the development of oral cancer are smoking and alcohol intake. The current challenge is to identify patients at greatest risk for the development of oral cancer using noninvasive and effective methods. The aim of this study is to evaluate the microsatellite mutations in the 9p21 locus, the cell proliferative activity, the pattern of epithelial desquamation, and the nucleus/cytoplasm ratio of exfoliated epithelial cells. Cytopathological samples were collected from 131 individuals divided into four groups: control ( n  = 26), alcohol-smoking ( n  = 32), leukoplakia ( n  = 38), and the oral squamous cell carcinoma group (OSCC, n  = 35). From the cytological scraping, a slide was silver impregnated for Ag-stained nucleolar organizer region analysis and another slide was stained using the Papanicolaou technique. The remaining cells were used for DNA extraction, followed by PCR amplification and capillary electrophoresis. The cell proliferation velocity rate was higher in the leukoplakia and OSCC groups compared with the control group ( P  < 0.05). The leukoplakia group showed increased anucleated scales, whereas the nucleated superficial predominated in the control group and the parabasal cells in the OSCC group ( P  < 0.05). An increased nucleus/cytoplasm ratio was detected only in the OSCC group ( P  < 0.05). The 9p21 locus mutation frequency was higher in the alcohol-smoking and leukoplakia groups. 9p21 analysis and Ag-stained nucleolar organizer region methods are promising for the screening and monitoring of individuals at higher risk for the development of oral cancer.